Energy‐efficient train timetabling for a medium‐speed maglev line considering propulsion and suspension energy consumption - Qingying Lai; Jun Liu; Shudong Guo; Xianliang Shi; Chen Zhao; Miaoyu Ju (IET Intelligent Transport Systems, 2023)
Abstract This paper addresses the energy‐efficient train timetabling problem for MSM systems, where both propulsion and suspension energy consumption are considered. The timetable design problem is modelled as a bi‐level model for a complete two‐way MSM line. The upper level determines the train departure time at the first station, which makes train operations more convenient for passengers. The lower level uses an empirical description of the train energy consumption as a function of segment running times, and an energy‐efficient timetable optimization model is built. In doing so, all the services in both directions along a certain planning horizon are considered while attending to a known passengers’ demand. Moreover, the convenience of considering energy consumption as part of a broad objective function that includes other relevant costs is pointed out. Then, a unified sequential solution algorithm is developed for an efficient and accurate solution of the bi‐level model. Experiments show that the proposed framework can generate a holographic timetable of energy‐efficient MSM containing multi‐dimensional variables such as time, space, velocity, and electrical quantities.